Pengaruh Brain Gym dan Resistance Exercise Pada Lansia dengan Kondisi Demensia Untuk Meningkatkan Fungsi Kognitif - Sari Triyulianti; Leila Ayuningtyas (LPPM Universitas Abdurrab, 2022)
ABSTRACT ABSTRACT Background: Dementia is a clinical syndrome characterized by progressive cognitive decline that interferes with the ability to function independently. Dementia is generally caused by disorders of some higher cortical functions, including memory, thought, orientation, understanding, learning, language, and assessment. Dementia is caused by various diseases and conditions that cause damaged of brain cells or connections between brain cells. The purpose of the study was to determine the effect of brain gym and resistance exercise to increase cognitive function in the elderly with dementia. Methods: Single case study with pre and post test design in 65 years old man with moderate cognitive impairment. Brain gym was carried out for 20 minutes, while resistance exercise was carried out for 60 minutes, three times a week for four weeks. The measurements used in this study used Mini Mental State Examination (MMSE) to evaluate the cognitive function in elderly. Results: After four weeks of treatment, the results showed an increase in cognitive function. The results of the initial measurement pre intervention obtained T0= 23, and at the post intervention T11= 25. Conclusion: The results of this study indicate that brain gym and resistance exercises can increase cognitive function in the elderly with dementia